Swati traditional healers'conceptualisation of causes and treatment of mental illness - Ngobe, A.J. (University of Limpopo, 2015)
The role of indigenous healers in managing various conditions of ill-health has been studied and debated. Studies have revealed that the majority of the population in South Africa use traditional health care to treat various mental conditions. Studies have also revealed that traditional medicine plays an important role in primary health care in many countries. The aim of the study was to explore Swati traditional healers’ conceptualization of the causes and treatment methods of mental illness in Kanyamazane Township in Mpumalanga Province, South Africa. A phenomenological research method was used in the present study. Ten (10) traditional healers, six (6) female and four (4) male, who were selected through purposive sampling method participated in the study. Semi structured personal interviews were conducted with the traditional healers. The interviews were conducted in siSwati and later translated to English. The main themes that emerged were grouped under the following 3 main topics: conceptualisation and types of mental illness; causes of mental illness; and, treatment of mental illness. The traditional healers identified and described a number of mental illnesses that could be identified by their behavioural symptoms and thought disruptions. These include: depressive conditions, addictions, psychotic illnesses, adjustment disorders and genetic mental illnesses. Mental illness was perceived to be caused by a number of factors that, among others, include the following: supernatural powers such as witchcraft, spirit possession, intrusion of objects, evil mechanisation, improper use of traditional medicine, disregarding ancestors and cultural customs as well invitation by ancestors to become a traditional healer, substance abuse, genetic predisposition, life stressors, social conditions, and injuries to the head, Cleansing the patient of evil spirits through washing, steaming, induced vomiting, casting out evil and herbal medication were some of the methods that were found to be commonly used to treat mental illness. The study found that the theory underlying traditional healing is essentially similar, and that traditional healers utilise a culturally coherent and holistic approach in dealing with health and illness.
Thesis ( M.A. (Psychology)) --University of Limpopo, 2015
Keywords: Traditional healers; Mental illness; Mental illness --Treatment --Swaziland; Healers